Intra-pancreatic release of bradykinin during the course experimental pancreatitis in rat - P. Jönsson; K. Ohlsson (Mediators of Inflammation)
Kallikrein/Kininogn activation is an important pathophysiological event in acute pancreatitis, leading to microcirculatory changes within the gland. Hitherto, only indirect measurements of pancreatic bradykinin formation have been performed, monitoring the peptide in the circulation and in the peritoneal exudate. In the present study, intra-pancreatic bradykinin release was assessed using microdialysis during experimental acute pancreatitis in rat. In mild, oedematous pancreatitis, induced by caerulein hyperstimulation, the levels of bradykinin within the gland were not elevated compared with those of control rats. However, in necrotic pancreatitis, induced by retrograde injection of taurocholate into the pancreatic duct, significantly elevated levels of intraglandular bradykinin were seen. Several rats in this group died whilst in a state of circulatory shock.